A comparison between patients with gastrointestinal stromal tumours diagnosed with isolated liver metastases and liver metastases plus sarcomatosis. Issue 9 (27th December 2012) - de la, Sebastian G.; Deneve, Jeremiah L.; Parsons, Colin M.; Zager, Jonathan S.; Conley, Anthony P.; Gonzalez, Ricardo J.
Abstract Objectives This study was conducted to compare overall survival (OS) in patients presenting with isolated hepatic metastases with that of patients with synchronous metastatic disease to the liver and sarcomatosis on a background of gastrointestinal stromal tumours (GISTs). Methods Patients presenting with metastatic GISTs during 1999–2009 were identified. Survival outcomes were compared between groups. Results Of the 193 patients with GISTs, 43 patients presented with isolated hepatic metastases and 16 presented with synchronous metastases to the liver and sarcomatosis. Thirteen patients with metastases to the liver and sarcomatosis underwent surgery, and 34 patients with metastatic disease solely to the liver underwent hepatic resection. The proportion of patients treated with preoperative tyrosine kinase inhibitor (TKI) therapy was similar in both groups. Similar OS was observed in both groups (isolated liver metastases group: 40.5 months; liver metastases and sarcomatosis group: 28.7 months; P = 0.620). Conclusions Overall survival in patients with GIST and metastatic disease to the liver and sarcomatosis is similar to that in patients with isolated metastatic liver disease. Although patients with a greater disease burden might be expected to show worse survival, these data do not reflect this assumption.